THE STORY OF ISRA' MI'RAJ PROPHET MUHAMMAD IN THE PERSPECTIVE OF SCIENCE - Ismail Adaramola Abdul Azeez,; Muhammad Afifuddin, (Rihlah Review: Jurnal Pendidikan Islam, 2025)
The purpose of this research is to analyze the journey of Isra' and Mi'raj of the Prophet Muhammad from a scientific perspective. The researcher uses descriptive qualitative with library research by analyzing related books and journals, where the data is obtained by studying the theme of Isra' Mi'raj in the perspective of science with in-depth study. After the data is collected, it is then analyzed with the concept and theory of Zero Kelvin. Through this study, it can be seen that the Zero Kelvin Theory and Heisenberg's Uncertainty Principle are so far suitable to explain the Isra' Mi'raj event, where the body of the Prophet Muhammad when traveling Isra' and Mi'raj traveled at the speed of light.Keywords: Prophet Muhammad, Heisenberg's uncertainty principle, isra', mi'raj, and the Kelvin Zero Theory.